(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
In order to talk about gender identity, we must first clarify terms from the sphere of Human Sexuality in order to delve into deeper issues and be able to understand them, because on many occasions we talk about terms such as sexual orientation, sexual identity, gender identity and sexual behavior without understanding the differences between them. The diagnosis of gender dysphoria focuses on emotional suffering as the problem, not on gender identity, occurring when a person has a notable incongruence between the sex experienced or expressed and the sex that was assigned at birth. In recent years, there has been a significant increase in gender dysphoria among adolescents and young adults, which has been called accelerated dysphoria, and this has made us question what the cause is, whether it is due to a better detection of cases to this depathologized and not having a social penalization or on the other hand what has been called a social contagion effect?.